HPV type 16 in conjunctival and junctional papilloma, dysplasia, and squamous cell carcinoma. Issue 12 (December 1995) - Saegusa, M; Takano, Y; Hashimura, M; Okayasu, I; Shiga, J
Abstract : AIMS--To clarify the role of human papillomavirus (HPV) infection in the development of papilloma, dysplasia, squamous cell carcinoma, and basal cell epithelioma arising from the eyelids, including the tunica conjunctiva palpebrum (conjunctiva), its junction to epidemis of eyelid skin (junction), and eyelid skin. METHODS--Sixteen cases of papilloma, four of dysplasia, four of squamous cell carcinoma, and 12 of basal cell epithelioma were examined using formalin fixed and paraffin embedded samples. Detection of HPV-DNA was performed by PCR-RFLP and in situ hybridisation (ISH) methods. RESULTS--HPV-16 was detected in 12/16 papillomas (75%), 2/4 dysplasias (50%), and 1/4 squamous cell carcinomas (25%) but in none of the basal cell epitheliomas. No other HPV subtypes were found. ISH assay showed positive signals in only two cases of dysplasia and squamous cell carcinoma. The mean age of HPV-16 positive dysplasia and squamous cell carcinoma cases (81.7 years) was significantly higher than that of HPV-16 positive papilloma cases (p < 0.01). CONCLUSIONS--Based on the presence of HPV-16 in both benign and malignant lesions and the age distribution, it seems likely that HPV-16 alone may be incapable of causing development of conjunctival and junctional dysplasia and squamous cell carcinoma, and that any correlation between the papilloma-squamous cell carcinoma sequence and HPV infection may be due to rare events.